The Impact of Teacher Experience and Motivation on the Performance of Elementary School Teachers in Wawo District, Bima, NTB - Patty, Elyakim Nova Supriyedi; Iriyani, Sri Astuti; Hadi, Heri Sopian; Marlina, Marlina; Ria, Reny Refitaningsih Peby (Universitas Nusantara PGRI Kediri, 2024)
This research aims to explain the following: (1) The joint impact of experience and motivation on teacher performance. (2) the impact of teacher experience on teacher performance and (3) the impact of teacher motivation on teacher performance in Wawo sub-district, Bima, NTB. The sample for this research consisted of 153 certified civil servant educators from Wawo District, Bima Regency. The